KHANDURI APAM: REPRESENTATION OF THEOLOGICAL VALUES IN ACEH’S LOCAL CULINARY BANQUET TRADITIONS - Suci Dihanna; Suci Fajarni; Taslim H.M. Yasin (International Conference on Social and Islamic Studies, 2021)
Khanduri Apam is one of the traditions or custom of banquets that has been passed down from generation to generation among the Acehnese, especially in Pidie Regency. The banquet was carried out by consuming local Aceh culinary, namely Apam cake (Serabi Cake in Bahasa) along with Aceh's typical tuhe sauce. As a society that is thick with Islamic values, Khanduri Apam was held with the aim of welcoming the month of Rajab as well as commemorating the Isra' Mi'raj event of the Prophet Muhammad Saw. Khanduri Apam is routinely held every seventh month in the Aceh calendar system, or what is known as Buleun Apam which is equivalent to Rajab Month in the Hijri Calendar. This study aims to describe the representation of theological values ​​contained in the implementation of the Khanduri Apam tradition among the people of Ulee Tutue Raya Village, Delima District, Pidie Regency, Aceh Province. The research method used is descriptive analytical qualitative method with data collection techniques in the form of observation, interviews, and documentation. The determination of informants is done by purposive sampling technique. The results of the study show that Khanduri Apam represents 5 theological values, namely: 1) divine values ​​(worship, alms); 2) social values ​​(togetherness, cooperation, tolerance); 3) spiritual value (commemorating Isra 'Mi'raj); 4) ritual values ​​(remembering and praying for the spirits); and 5) intellectual values ​​(preserving customs as well as local cuisine). Regarding the representation of intellectual values, Dinas Pendidikan dan Kebudayaan of Pidie Regency also participated by instructing all schools in Pidie Regency, from kindergarten, elementary, to junior high education levels, to hold Khanduri Apam in the school environment as an effort to maintain the continuity of this tradition among the younger generations, so that they can recognize and maintain these traditions in the midst of the onslaught of contemporary culinary. The Khanduri Apam tradition has a rooted relevance to Islamic religious values ​​which are considered not contrary to Islamic Sharia Law. So that the dialectic of Islam with cultural realities will continue to be intertwined with the values ​​of Islamic theology throughout its history.